2022
DOI: 10.3390/ijerph19031816
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Newly Admitted to Long-Term Care Facilities among Older Adults with Disabilities in Taiwan

Abstract: This study aimed to explore the lived experiences of Taiwanese older adults with disabilities newly admitted to long-term care facilities (LTCFs). A descriptive phenomenological method was used. Colaizzi’s method analysis of 15 participant interviews revealed six themes: “living here is a last resort”, “I don’t like it but still have to live here”, “my needs are not understood”, “looking forward to emotional support”, “practicing the way of survival”, and “trying to make myself better”. The older adults were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Fourteen themes emerged and, within each theme, the researchers examined the meaning of the lived experiences. 35 They examined the data for co-occurrence, the intersection of two themes, in order to explore the association between thematic concepts and the meaning of the phenomena. 36 With high co-occurrence, intersecting theme pairs with the highest number of co-occurrences across all four listening sessions, the study identified dominant themes and significant shared experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen themes emerged and, within each theme, the researchers examined the meaning of the lived experiences. 35 They examined the data for co-occurrence, the intersection of two themes, in order to explore the association between thematic concepts and the meaning of the phenomena. 36 With high co-occurrence, intersecting theme pairs with the highest number of co-occurrences across all four listening sessions, the study identified dominant themes and significant shared experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Asian cultures, including Taiwan, have regarded the care of older adults as an essential responsibility of the family (Chien et al, 2022). Prior to 1960, nearly all older relatives in Taiwan were cared for by family members due to cultural demands including reciprocity, filial piety, debt reduction (karma) and equity of shared responsibility (Hsu & Shyu, 2003).…”
Section: Introductionmentioning
confidence: 99%